1977
DOI: 10.1073/pnas.74.5.1846
|View full text |Cite
|
Sign up to set email alerts
|

Neurotensin: specific binding to synaptic membranes from rat brain.

Abstract: The binding of neurotensin to synaptic membranes from rat brain was studied at 24°with the use of [3HJ neurotensin. The binding was found to be highly specific, saturable, and reversible. Values for KD of 2 nM and 0.9 nM were derived from equilibrium and kinetic experiments, respectively. Virtually no degradation of neurotensin was observed in the incubation medium after exposure to synaptic membranes under the conditions of the binding studies. Competitive inhibition of [3Hlneurotensin binding by partial sequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
77
0

Year Published

1979
1979
2009
2009

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 177 publications
(89 citation statements)
references
References 14 publications
(12 reference statements)
12
77
0
Order By: Relevance
“…However the most active compound in preventing '2I-apamin association to its receptor is neurotensin. This neuropeptide of 13 amino acids has two contiguous arginines in its active site (22).t Other charged molecules like verapamil also interfere with '"I-apamin binding to the neuroblastoma membrane.…”
Section: Resultsmentioning
confidence: 99%
“…However the most active compound in preventing '2I-apamin association to its receptor is neurotensin. This neuropeptide of 13 amino acids has two contiguous arginines in its active site (22).t Other charged molecules like verapamil also interfere with '"I-apamin binding to the neuroblastoma membrane.…”
Section: Resultsmentioning
confidence: 99%
“…Fig. 4 with an order of potency identical to the neurotensin receptor expressed in the HT29 cell line [6] and other tissues [14]: (i) neurotensin is the most potent competitor, followed by neuromedin N and SR 48692; (ii) the apparent half maximal concentrations for an inhibition (IC,,) derived from the competition curves were 0.3, 2.6 and 38 nM, respectively; and (iii) levocabastine, an anti-histamine agent described as a ligand for the low affinity neurotensin binding site [22] does not compete (using concentrations up to 10 PM) with "SI-labeled [monoiodo-Tyr3] neurotensin for the binding to COS cells, demonstrating that the transfected cDNA encodes a high affinity NTR.…”
Section: Pharmacological and Functional Characterization Of Cloned Hntrmentioning
confidence: 99%
“…The biochemical and pharmacological properties of these binding sites have been extensively studied using mammalian brain homogenates as well as membrane preparations from neuronal and certain non-neuronal cell lines [5,6]. It has been shown that the interaction with these receptors modulates intracellular levels of cGMP, CAMP and inositol phosphates [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…5, Table 4). [6,20] and that receptor occupancy leads to inositol phosphate formation [6]. The present work was designed variations using the fluorescent indicator quin 2 [9] showed that neurotensin (0.…”
Section: -Neurotensin Binding To Ht29 Cell Homogenatesmentioning
confidence: 99%